ANALISIS REAKSI PASAR MODAL TERHADAP PERISTIWA PENGUMUMAN MERGER BANK SYARIAH (Event Study pada Saham BRI Syariah): Event Study pada Saham BRI Syariah - Mentari Permata Suci (CV ODIS, 2021)
The purpose of this case study is to determine the reaction of the capital market to the announcement of sharia bank mergers. The variables used to measure market reactions are abnormal returns and trading volume activity. The sample in this study is BRI sharia stocks. The research was conducted during the observation period 20 days before the incident, one day at the time of the incident, and 20 days after the event. The analysis used is the Wilcoxon test analysis. This study shows that the merger of sharia state-owned banks has no impact on the capital market. There is no difference in the average transaction volume activity (ATVA) before and after the announcement of the merger of Sharia SOEs on October 12, 2020. However, there is abnormal difference in return before and after the announcement of the merger of Sharia State-Owned Banks. This finding is due to the limited observation period so that the impact of the observed events is not too broad and the effect of events on the company's shares is less known.